2017
DOI: 10.1021/acs.bioconjchem.7b00056
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Populations Evolve to Resist CdSe Quantum Dot Toxicity

Abstract: Engineered nanomaterials are used globally in biomedical, electronic, and optical devices, and are often discarded into the environment. Cell culture experiments have shown that many inorganic nanoparticles are toxic to eukaryotic cells. Here, we show that populations of eukaryotic cells can evolve to survive chronic exposure to toxic CdSe semiconductor quantum dots (QDs). We grew yeast Saccharomyces cerevisiae for 24 days in liquid medium containing QDs prepared daily at half the minimum inhibitory concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…For example, TRK1 is a gene encoding for a structural component of the Trk1p−Trk2p complex K + transport system; 70 Smith et al 71 observed that a Δtrk1 mutant was resistant to functionalized Au NPs treatment. Strtak et al 72 grew S. cerevisiae for 24-days (for 100 generations) in the presence of CdTe QDs at half the minimum inhibitory concentration (MIC 50 ) of the wild type strain; the authors noted that this exposure led to the selection of resistant Δbul1 mutated strains that showed a higher fitness in the presence of QDs. BUL1, like DSK2, has an important role in polyubiquitination in yeast; 73 specifically, it is involved in mediating the transfer of the ubiquitin.…”
Section: ■ the Mitochondrial Role In Enms Responsementioning
confidence: 99%
“…For example, TRK1 is a gene encoding for a structural component of the Trk1p−Trk2p complex K + transport system; 70 Smith et al 71 observed that a Δtrk1 mutant was resistant to functionalized Au NPs treatment. Strtak et al 72 grew S. cerevisiae for 24-days (for 100 generations) in the presence of CdTe QDs at half the minimum inhibitory concentration (MIC 50 ) of the wild type strain; the authors noted that this exposure led to the selection of resistant Δbul1 mutated strains that showed a higher fitness in the presence of QDs. BUL1, like DSK2, has an important role in polyubiquitination in yeast; 73 specifically, it is involved in mediating the transfer of the ubiquitin.…”
Section: ■ the Mitochondrial Role In Enms Responsementioning
confidence: 99%
“…In order to establish proper approaches to overcome the heavy metal toxicity, hydrophobic attachment, and simplex dimension during investigating the possible candidates, resultant should be acceptable in maintaining relatively optical properties, and understandable in fabricating procedures . One factor is that heavy or precious metal elements are not utilized in convenient synthetic works for environmental and inexpensive targets.…”
mentioning
confidence: 99%
“…Thus, our results are in line with previous studies. Still, it is a somewhat unexpected result, considering that these particles have been commercially produced for biotracking purposes, and many studies do report QDs entering cells [ 60 , 61 , 62 , 63 , 64 ]. Plant studies have shown that particles with a positive charge are more readily taken up and translocated than those with a negative charge [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%